Guanine condensates as covalent materials and the concept of cryptopores - Kossmann, Janina; Piankova, Diana; Tarakina, Nadezda; Heske, Julian; Kühne, Thomas D.; Schmidt, Johannes; Antonietti, Markus; Lopez-Salas, Nieves (Carbon, 2021)
Simple thermal treatment of guanine at temperatures ranging from 600 to 700 °C leads to C1N1 condensates with unprecedented CO2/N2 selectivity when compared to other carbonaceous solid sorbents. Increasing the surface area of the CN condensates in the presence of ZnCl2 salt melts enhances the amount of CO2 adsorbed while preserving the high selectivity values and C1N1 structure. Results indicate that these new materials show a sorption mechanism a step closer to that of natural CO2 caption proteins and based on metal free structural cryptopores.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon dioxide capture; CN; Cryptopores